A terra que virou poesia: A arte da cerâmica em Toshiko Ishii - Marcia Norie Seo (2009)
In this study I propose to approach the universe of Toshiko Ishii, an important ceramic artist in Belo Horizonte, from various point of views: the memory of those who were close to her life and work, the physical traces of his existence as her pieces and place of work. These allow us to construct an image of Toshiko to inspire a ceramic collection that I develop myself as part of the dissertation. Toshiko's work embodies the beauty of simplicity, while exploring new forms of expression from the style that she calls: Bizen Mineiro. The ceramic reflects, in a subtle way, the very existence of the artist ensuring their last in time and itsprojection over those who are in touch with her work.